Nucleolar residence of the seckel syndrome protein TRAIP is coupled to ribosomal DNA transcription. Issue 19 (27th August 2018) - Chen, Yangzi; Li, Junshi; Cao, Fakun; Lam, Jason; Cheng, Clooney CY; Yu, Cheng-han; Huen, Michael SY
Abstract: The RING finger protein TRAIP protects genome integrity and its mutation causes Seckel syndrome. TRAIP encodes a nucleolar protein that migrates to UV-induced DNA lesions via a direct interaction with the DNA replication clamp PCNA. Thus far, mechanistically how UV mobilizes TRAIP from the nucleoli remains unknown. We found that PCNA binding is dispensable for the nucleolus-nucleoplasm shuttling of TRAIP following cell exposure to UV irradiation, and that its redistribution did not rely on the master DNA damage kinases ATM and ATR. Interestingly, I-PpoI-induced ribosomal DNA damage led to TRAIP exclusion from the nucleoli, raising the possibility that active ribosomal DNA transcription may underlie TRAIP retention in the nuclear sub-compartments. Accordingly, chemical inhibition of RNA polymerase I activity led to TRAIP diffusion into the nucleoplasm, and was coupled with marked reduction of DNA/RNA hybrids in the nucleoli, suggesting that TRAIP may be sequestered via binding to nucleic acid structures in the nucleoli. Consistently, cell pre-treatment with DNase/RNase effectively released TRAIP from the nucleoli. Taken together, our study defines a bipartite mechanism that drives TRAIP trafficking in response to UV damage, and highlights the nucleolus as a stress sensor that contributes to orchestrating DNA damage responses.